Bioelectrochemical recovery of waste-derived volatile fatty acids and production of hydrogen and alkali. (15th September 2015) - Zhang, Yifeng; Angelidaki, Irini
Abstract: Volatile fatty acids (VFA) are organic compounds of great importance for various industries and environmental processes. Fermentation and anaerobic digestion of organic wastes are promising alternative technologies for VFA production. However, one of the major challenges is development of sustainable downstream technologies for VFA recovery. In this study, an innovative microbial bipolar electrodialysis cell (MBEDC) was developed to meet the challenge of waste-derived VFA recovery, produce hydrogen and alkali, and potentially treat wastewater. The MBEDC was operated in fed-batch mode. At an applied voltage of 1.2 V, a VFA recovery efficiency of 98.3%, H2 of 18.4 mL and alkali production presented as pH of 12.64 were obtained using synthetic fermentation broth. The applied voltage, initial VFA concentrations and composition were affecting the VFA recovery. The energy balance revealed that net energy (5.20–6.86 kWh/kg-VFA recovered) was produced at all the applied voltages (0.8–1.4 V). The coexistence of other anionic species had no negative effect on VFA transportation. The VFA concentration was increased 2.96 times after three consecutive batches. Furthermore, the applicability of MBEDC was successfully verified with digestate. These results demonstrate for the first time the possibility of a new method for waste-derived VFA recovery and valuable products production that uses wastewater as fuel and bacteria as catalyst. Graphical abstract: Highlights: An innovative technology for waste-derived VFA recovery and bioenergy production. The voltage, initial VFA levels and composition were affecting the recovery. Net energy (≥5.20/kg-VFA) was produced at the applied voltages between 0.8 and 1.4 V. The coexistence of anionic species had no negative effect on VFA transportation. The VFA was concentrated by 2.96 times after three consecutive batches.